Tacinga inamoena vegetal drug characterization using phytochemistry, pharmacopoeial methods and thermoanalytical techniques - Joanda Paolla Raimundo e Silva; Malu Maria Lucas dos Reis; Cleildo Pereira Santana; Ana Cláudia Dantas de Medeiros; Harley da Silva Alves (Universidade de São Paulo, 2021)
Tacinga inamoena (K. Schum.) N.P. Taylor & Stuppy, also known as quipá, is a native cactus of the Caatinga used in traditional medicine to treat urethral infections and inflammation. This study aimed to determine the physicochemical characteristics of vegetal drug obtained from the roots of T. inamoena. Analytical techniques and phytochemical tests were used, such as thermal analysis, qualitative and semiquantitative determination of secondary metabolites and spectroscopy at the infrared region. The powder of the vegetal drug met the parameters established by the Brazilian Pharmacopoeia, except for compressibility, which was low. On the thermogravimetric curve, three events related to the mass loss were verified, which correlate with the vegetal drug quality control and play a part in their standardization. The qualitative screening suggested the presence of alkaloids, flavonoids and terpenes. The infrared spectrum reinforced the presence of hydroxyl, carbonyl, and ether groups. In the semiquantitative screening, a concentration for total polyphenols of 65 mg equivalent to gallic acid g-1 to the crude ethanol extract (CEE) was obtained. On the correlation of flavonoid content to seasonality, a concentration was obtained of 3.3 mg equivalent to quercetin g-1 to the CEE obtained during the drought period and of 10.6 mg equivalent to quercetin g-1 to the CCE obtained during the rainy season. In T. inamoena, the presence of important classes of secondary metabolites, which are associated with the pharmacognostic characterization, aids the authentication and quality control of vegetal drugs of importance in traditional Brazilian medicine.